PERBEDAAAN KETERSEDIAAN PANGAN PANTI, TINGKAT KECUKUPAN ENERGI-PROTEIN DAN STATUS GIZI LANSIA PEREMPUAN ANTARA PANTI WREDHA NEGERI DAN SWASTA (Studi di Unit Rehabilitasi Sosial Pucang Gading Provinsi Jawa Tengah dan Panti Wredha Harapan Ibu Kota Semarang) - Yulinar Tri Pamungkas; Laksmi Widajanti; Sri Achadi Nugraheni; M. Zen Rahfiluddin (Jurnal Kesehatan Masyarakat, 2019)
ABSTRACTPrevious studies found nutritional status in the underweight category of Homecare compared with elderly living in non-homecare dominated by women.7Purpose of the study was to analyze differences between National Homecare (NH) and Private Homecare (PH) of the food availability, Energy-Protein Sufficiency Level(ESL-PSL) and nutritional status of elderly women. The research method uses a cross sectional approach. The sampling technique use Stratified sampling method with the inclusion and exclusion criteria of elderly women in NH and PH for 30 and 32 subjects. Data analysis used different tests: Chi Square, Mann Whitney U and Independent Sample T-Test. The results showed that there isdifference of food availability between NH and PH (p=0,001) with average food availability of NH (84,5) hinger then NH (65). There is a difference in the ESL of elderly women (p = 0.001) between NH and PH with ESL average NH (75,74±5,32) hinger then PH (61,11±7,20). There is a difference of elderly women PSL (p = 0.001) between NH and PH with (83,167±4,82) hinger then PH (72,14±6,44). And there is no difference in the nutritional status of elderly women based on Body Mass Index (BMI) (p = 0.125) between NH and PH with average of NH (20,01±3,86) lower then PH (22,99±4,65). There was no difference in nutritional status based on the circumference of the elderly abdominal women (p = 0.359) between NH and PH with average (61,11±7,30) lower then NH (75,74±5,32).. It can be concluded that there are differences in the variables of food availability, the ESL,-PSL in elderly women and there is no difference in nutritional status based on BMI and the stomach circumference of elderly women between NH and PH.